Research in Psychotherapy. 1968
DOI: 10.1037/10546-017
|View full text |Cite
|
Sign up to set email alerts
|

Speech and silence behavior in clinical psychotherapy and its laboratory correlates.

Abstract: low status; and high activity/high status. Procedural checks suggested that experimental manipulations were successful, and significant relationships were found between interviewer and S reaction time latency and between S trust and revealingness. The predicted relationships between interviewer and S duration of utterance and the experimental conditions and revealingness were not found. There is need for further study of the effects of "noncontent" verbal behaviors in combination upon noncontent verbal behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1970
1970
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 8 publications
1
39
0
Order By: Relevance
“…Mimicking others probably plays an important role in speech development (Abravanel & Sigafoos, 1984; Abravanel & DeYong, 1991) and adult humans adapt their speech behaviors to others in their environment, including speech rate and utterance length (Matarazzo, Weins, Matarazzo, & Saslow, 1968; Webb, 1972; Cappella & Planalp, 1972). Given that speech entrainment elicits fluent speech production in some aphasic patients whereas the same effect is not seen in actual speech repetition, it is clear that the real-time synchrony between the speech model and the entrained speaker is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Mimicking others probably plays an important role in speech development (Abravanel & Sigafoos, 1984; Abravanel & DeYong, 1991) and adult humans adapt their speech behaviors to others in their environment, including speech rate and utterance length (Matarazzo, Weins, Matarazzo, & Saslow, 1968; Webb, 1972; Cappella & Planalp, 1972). Given that speech entrainment elicits fluent speech production in some aphasic patients whereas the same effect is not seen in actual speech repetition, it is clear that the real-time synchrony between the speech model and the entrained speaker is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…When speaking, conversants typically use more illustrative gestures than they do when listening (Duncan & Fiske, 1977). The evidence of turn duration compensation is a common finding in interviews (Matarazzo, Wiens, Matarazzo, & Saslow, 1986; and conversation (Street & Murphy, 1987) and is likely due to the cyclical nature of floor-holdings as speakers exchange periods of being the dominant speaker. For example, during the first part of the medical interview, the patient may exhibit relatively long speaking turns and frequent gestures (e.g., explaining the problem) while the physician acts as a facilitator-listener.…”
Section: General Trendsmentioning
confidence: 91%
“…Modifications may occur at any linguistic level, including language complexity (as when people simplify their language when speaking to babies or foreigners [10]), politeness [5], accent [11], and choice of language [13]. Especially relevant to the present study, speakers have also been found to accommodate to one another in extra-linguistic behaviors such as utterance length [24], speech rate [31], pause length [18], and response latency [8].…”
Section: Accommodationmentioning
confidence: 99%